Mastering pandas for finance : master pandas, an open source Python data analysis library, for financial data analysis - Heydt, Michael (Community experience distilled., 2015)
If you are interested in quantitative finance, financial modeling, and trading, or simply want to learn how Python and pandas can be applied to finance, then this book is ideal for you. Some knowledge of Python and pandas is assumed. Interest in financial concepts is helpful, but no prior knowledge is expected.